The type of androgenetic alopecia and quality of life (QoL) in male patients - Khairina Nasution; Raynald Pradigo; Rudi Chandra (Universitas Gadjah Mada, 2022)
Androgenetic alopecia (AGA) is a nonscarring baldness that mostly affects >50% men worldwide. Hair loss led to psychological difficulties and have a negative impact on the quality of life (QoL). This study aimed to evaluate the relationship between the type of AGA and QoL in male patients. A total of 67 male AGA patients were clinically assessed using the Hamilton-Norwood scale and interviewed using the Hair-Specific Skindex-29 scale to assess QoL. The patients were predominantly in the age group 31-50 years (50.7%), mean age 49.60 years, grade I obese (32.8%), mean BMI 24.93 kg/cm2, 41.8% with father’s AGA history, smoking (62.7%), smoking >100 cigarettes in last 6 months (41.8%), and have hypertension (16.4%) and diabetes mellitus (3%) as concomitant diseases. Based on Noorwood-Hamilton scale, the types of AGA were predominantly type II (25.4%) and followed by type III (16.4%). The results of the Hair Specific Skindex-29 on AGA patients were moderate (58.2%) and severe (41.8%). There were a relationship between AGA type and QoL (p = 0.041) and significant positive correlation between AGA type and QoL (p = 0.020, r = 0.282). In conclusion, patients experienced moderate to severe impact on QoL due to AGA. Thus, every increased in the type of AGA will impact patient’s quality of life.Androgenetic alopecia (AGA) is a nonscarring baldness that mostly affects >50% men worldwide. Hair loss led to psychological difficulties and have a negative impact on the quality of life (QoL). This study aimed to evaluate the relationship between the type of AGA and QoL in male patients. A total of 67 male AGA patients were clinically assessed using the Hamilton-Norwood scale and interviewed using the Hair-Specific Skindex-29 scale to assess QoL. The patients were predominantly <span style=